The association between dietary diversity and hearing loss: results from a nationwide survey - Du, Qiaoqiao; Yang, Haizhen; Zhang, Hua; Yao, Yao; Wen, Zhongmin; Zhu, Xiaojun; Gao, Xiangyang (Frontiers in Nutrition, 2025)
BackgroundHearing loss is a leading cause of disability among older adults. Previous studies have suggested that dietary factors may play a role in preventing hearing loss. However, findings remain inconsistent, and longitudinal evidence is limited. Based on a national sample, this study aims to explore the association between the different dietary diversity score (DDS) and hearing loss in the older adult Chinese population.MethodsWe analyzed longitudinal data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) spanning 2011 to 2018. The study recruited participants aged 60 years and older from the 2011 and 2014 CLHLS waves, with follow-up assessments in 2014 and 2018. Hearing loss was assessed through a questionnaire, while dietary diversity was evaluated using four DDS indicators: total diet, animal-based diet, protein-based diet, and plant-based diet. Cox regression models were employed to examine the relationship between various DDS categories and hearing loss, with adjustments for confounding factors. Restricted cubic spline (RCS) regression was employed to explore the relationship between DDS and hearing loss. Subgroup analyses and sensitivity analyses were performed to further validate the findings.ResultsThe cohort study included 3,839 older adults (mean age 79.1 ± 9.3 years) without hearing loss at baseline, comprising 1874 males (48.8%) and 1965 females (51.2%). The mean follow-up duration was 4.2 years (SD 1.9). The incidence of hearing loss was 47.6% (1827/3839). After adjusting for confounding factors, higher plant-based DDS (HR = 0.783; 95% CI: 0.637–0.962, P-trend = 0.027) was associated with a reduced risk of hearing loss. The RCS analysis indicated a negative linear association between plant-based DDS and hearing loss (p for linearity = 0.014). Sensitivity analysis further verified the robustness of the above findings. Similar results were observed in adults aged ≥80 years, males, and individuals without hypertension, diabetes, or heart disease.ConclusionDietary diversity in plant-based diet serves as a protective factor against hearing loss in the older adult population. Adopting a diversified plant-based diet may help reduce the risk of hearing loss among older adults.